Fatty acid content and profile of round sardinella (Sardinella aurita), an expanding thermophilic species in the NW Mediterranean - VILA-BELMONTE, MAR; BOU, RICARD; LLORET, ELSA; LLORET, JOSEP (Mediterranean Marine Science, 2024)
Over the past few decades, due to sea warming driven by global climate change, the habitat range of round sardinella (Sardinella aurita) has expanded into the north-western Mediterranean Sea. This study evaluates the fatty acid content and fatty acid profile of this small, warm-water pelagic fish caught in this area, specifically the northern Catalan coast. The findings provide important insights into the nutritional status of the species under changing environmental conditions. The study confirms that fatty acid content varies according to the individual specimen’s maturity stages (immature, pre-spawners, and spawners). Pre-spawners showed higher fat levels compared to spawners, whose lipids are allocated to their gonads to enhance the survival of their offspring. While a high content of omega-3 polyunsaturated fatty acids (n-3 PUFAs) was generally found at all stages of maturity, pre-spawners had higher levels of EPA but lower levels of DHA than immature individuals and spawners. Moreover, compared to small pelagic fish more typical of the temperate waters in the region (European anchovy, Engraulis encrasicolus, and European sardine, Sardina pilchardus), round sardinella generally have a higher level of PUFAs, especially DHA. Encouraging consumption of this warm water species could provide significant nutritional benefits while reducing fishing pressure on European sardine and European anchovy, whose populations are currently in a very poor state.